The association between socioeconomic status, oral hygiene practice, denture stomatitis and oral status in elderly people living different residential homes - EVREN, BUKET; ÖZKAN, YASEMİN (ELSEVIER IRELAND LTD, 2011)
Oral hygiene practices and denture status of elderly people living in residential homes are different depending on the type of residential homes. In this study the elderly people living in three different residential homes were investigated for this purpose. A total of 269 subjects, 119 males (mean age 73.9 + 8.8) and 150 females (mean age 78.5 + 7.2) were involved in this study. All subjects were interviewed and clinically examined. Age, sex, educational status, financial status, general health, dental visiting, overnight denture wearing, brushing habits and frequency were recorded using a structured questionnaire. The prevalence of edentulism, the presence and type of dental prostheses, denture cleanliness and the presence of denture stomatitis were evaluated. Forty-one percent of subjects were non-educated. Fifty-one percent of subjects had low income. The majority of people (66.6%) were edentulous. Among the edentulous subjects 32% had full denture and 16% had no denture. Forty three percent of the subjects reported cleaning their dentures with water and 40% with a toothbrush only. Denture hygiene was good for 14% of the subjects. Denture stomatitis was observed in 44% of the subjects wearing dentures. There was statistically significant difference between residential homes and educational status, level of income, dental visiting, denture status, brushing methods and brushing frequency (p < 0.001). A positive relationship was observed between poor denture hygiene habits and the presence of denture-related stomatitis. The most important need within the residents of the residential home was the enhancement of oral care social insurance. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: Elderly people; Denture status; Denture stomatitis; Residential homes; HEALTH PROGRAM; CLEANLINESS; EDENTULISM; POPULATION; HABITS; TURKEY; YEASTS